BATAS WAKTU MUSAFIR BERMUKIM UNTUK KEBOLEHAN QASAR SALAT - Yenny Sri Wahyuni; Yusrizal Bin Razali (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2019)
The traveler is one of the reasons that allows someone to pray qasar, this is the opinion that has been agreed by the scholars. They differ in opinion as to how long a traveler is allowed to pray. In this case, the Hanafi school argues that the traveler is allowed to pray continuously, unless he has lived in a place for more than 15 days, then he is considered a mukim and must complete his prayer. Meanwhile, the Syafi'i mazhab of the traveler is allowed to qasar continuously, unless he stays in a place for more than 3 days. The research question is: what is the istinbat method used by the Hanafi and Syafi'i schools in determining the time limit of the qasar's allowance for the traveler and what is the reason for the differences of opinion between these two schools of thought. The research method that the author uses is a comparative descriptive method, namely research by analyzing and comparing opinions, reasons and interpretations of the arguments used as a basis for the opinion of the school of thought. The results found are that both schools use the method of istinbat bayani. The cause of differences in opinion is due to the confusion of the dhahir in a number of hadiths and the subjectivity of the mujtahid in understanding the texts.